Mendelian randomization analyses of smoking and Alzheimer’s disease in Chinese and Japanese populations - Zhu, Yuan; Guan, Ying; Xiao, Xuewen; Jiao, Bin; Liao, Xinxin; Zhou, Hui; Liu, Xixi; Qi, Feiyan; Peng, Qiyuan; Zhou, Lu; Xu, Tianyan; Yang, Qijie; et al. (Frontiers in Aging Neuroscience, 2023)
Background: Previous epidemiological studies have reported controversial results on the relationship between smoking and Alzheimer's disease (AD). Therefore, we sought to assess the association using Mendelian randomization (MR) analysis. Methods: We used single nucleotide polymorphisms (SNPs) associated with smoking quantity (cigarettes per day, CPD) from genome-wide association studies (GWAS) of Japanese population as instrumental variables, then we performed two-sample MR analysis to investigate the association between smoking and AD in a Chinese cohort (1000 AD cases and 500 controls) and a Japanese cohort (3962 AD cases and 4074 controls), respectively. Results: Genetically higher smoking quantity showed no statistical causal association with AD risk (the inverse variance weighted (IVW) estimate in the Chinese cohort: odds ratio (OR) = 0.510, 95% confidence interval (CI) = 0.149 - 1.744, P = 0.284; IVW estimate in the Japanese cohort: OR = 1.170, 95% confidence interval CI = 0.790 - 1.734, P = 0.434). Conclusion: This MR study, for the first time in Chinese and Japanese populations, found no significant association between smoking and AD.